A novel, multi-component contingency management intervention in the context of a syndemic of drug-related harms in Glasgow, Scotland: First year of the ‘WAND’ initiative - S. Smith; K.M.A. Trayner; J. Campbell; A. McAuley; J. Craik; C. Hunter; S. Priyadarshi; S.J. Hutchinson (Addictive Behaviors Reports)
Background: To address high levels of drug-related harms among people who inject drugs (PWID) in Glasgow, a novel contingency management intervention was developed to engage high-risk PWID with four harm reduction measures (known as the WAND initiative: Wound care, Assessment of injecting, Naloxone, and Dried blood-spot test). Our aims were to assess if WAND engaged and re-engaged high-risk PWID. Methods: Baseline data of WAND participants (n = 831) from 1st Sept-2020 to 30th Aug-2021 were analysed. For those who took part in the first six months, extent of re-engagement was determined and, among those re-engaged, intervention coverage was compared between baseline and final engagement. Results: Among those who first engaged in WAND from Sept 2020-Feb 2021 (n = 546), 40 % re-engaged by Aug 2021. Compared to those who engaged once (n = 321), those who re-engaged (n = 215) within one year had higher baseline prevalence of injecting risk behaviours such as injecting daily (56 % vs 64 %, p = 0.032), injecting away from home (42 % vs 52 %, p = 0.0179), injecting cocaine (56 % vs 75 %, p < 0.001), having an SSTI (40 % vs 60 %, p < 0.001), and been prescribed naloxone (57 % vs 72 %, p < 0.001). For those who re-engaged six months to one year after initial engagement (n = 107), there was a significant increase in having a BBV test in the last six months (61 % to 81 %, p = 0.003) and carrying naloxone (22 % to 32 %, p = 0.011). Conclusion: WAND was able to engage and re-engage large numbers of high-risk PWID with multiple harm reduction initiatives. These findings suggest contingency management could be a useful tool for harm reduction services.